Neomorphic PDGFRA extracellular domain driver mutations are resistant to PDGFRA targeted therapies. Issue 1 (December 2018) - Ip, Carman; Ng, Patrick; Jeong, Kang; Shao, S.; Ju, Zhenlin; Leonard, P.; Hua, Xu; Vellano, Christopher; Woessner, Richard; Sahni, Nidhi; Scott, Kenneth; Mills, Gordon
Abstract Activation of platelet-derived growth factor receptor alpha (PDGFRA) by genomic aberrations contributes to tumor progression in several tumor types. In this study, we characterize 16 novelPDGFRA mutations identified from different tumor types and identify three previously uncharacterized activating mutations that promote cell survival and proliferation. PDGFRA Y288C, an extracellular domain mutation, is primarily high mannose glycosylated consistent with trapping in the endoplasmic reticulum (ER). Strikingly, PDGFRA Y288C is constitutively dimerized and phosphorylated in the absence of ligand suggesting that trapping in the ER or aberrant glycosylation is sufficient for receptor activation. Importantly, PDGFRA Y288C induces constitutive phosphorylation of Akt, ERK1/2, and STAT3. PDGFRA Y288C is resistant to PDGFR inhibitors but sensitive to PI3K/mTOR and MEK inhibitors consistent with pathway activation results. Our findings further highlight the importance of characterizing functional consequences of individual mutations for precision medicine. Activation of PDGFRA by genomic aberrations contributes to tumor progression in several tumor types. Here, the authors perform functional characterization of 16 novel PDGFRA mutations identified from different tumor types and demonstrate that a neomorphic PDGFRA extracellular domain driver mutation is resistant to PDGFRA targeted therapies.